Chromosome number of three Bambusa species (Poaceae) in northeastern communities of Thailand (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Saensouk P, Saensouk S, Sudchaleaw S, Sungkaew S. 2023. Chromosome number of three Bambusa species (Poaceae) in northeastern communities of Thailand. Biodiversitas 24: 4544-4547. Bambusa is a genus within subfamily Bambusoideae, family Poaceae. This study aimed to conduct the chromosome numbers of three Bambusa species in the northeastern Communities of Thailand. All three Bambusa species were studied with somatic chromosome numbers from root tips by squash methods. The somatic chromosome numbers, ploidy, and chromosome size in length from the root tips of three Bambusa species are provided. The somatic chromosome numbers range from 2n = 56 to 2n = 72. Bambusa bambos (L.) Voss was reported as 2n = 56 with high ploidy (heptaploid or 7x), B. burmanica Gamble was reported to be 2n = 72 with high ploidy (nonaploid or 9x), and B. tuldoides Munro was investigated to be 2n = 64 with high ploidy (octaploid or 8x). The basic chromosome number of three Bambusa species studied was x=8. The chromosome numbers of B. burmanica was studied for the first time. The chromosome length of all species was very short between 0.80 µm in B. burmanica and 1.30 µm in B. bambos.
Keywords: Bambusa, bamboo, chromosome number, Poaceae, Thailand